PERDEBATAN TAQLID DALAM ‘AQIDAH DAN SHARI‘AH - Imanuddin Abil Fida (IMTIYAZ: Jurnal Ilmu Keislaman, 2019)
The debates on the subject of imitation (taqlid) does not exist in the field of fiqih, but also in ushuluddin. Moreover, regarding permissibility of taqlid has been discussed by scholars since the second century. The debate has been more intense after the fall of Baghdad. Some argues that Baghdad’s fall was due to the rise of taqlid among Muslims. Therefore, various books have been written to encourage for ijtihad in order to grow the spirit of knowledge. While others wrote concerning the reason for rejection taqlid based on al-Qur’an, hadist and logic. This article will explain the views of scholars around taqlid both in ‘aqidah and syari’ah